Design of reinforced concrete truss systems in earthquake-resistant high-rise buildings - Paikun; Pirmansyah; Cece Suhendi; Triono; Niels vuegen (Nusa Putra University, 2021)
This study aims to find out how to plan the Reinforced Concrete Bar Frame Structure which includes the structure of columns and beams and their reinforcement to meet the design concept of capacity, namely strong columns and weak beams. In this study, it will be planned on the Nusa Putra Islamic Boarding School building which amounts to 3 floors using the Special Moment Resistant Frame System (SRPMK) in accordance with SNI-2847-2013 and SNI-1726-2012. The earthquake load used is Spectrum Response Analysis by taking into account three different types of soil conditions namely hard, medium and soft soils. Moment Resistant Frame System is a spatial frame system in which structural components and their joints resist forces acting through bending, sliding and axial action. The quality of the concrete material used is 25 MPa and the reinforcing steel material used 400 MPa threaded iron while the beam dimensions are 300 mm x 400 mm and the column is 500 mm x 500 mm. The results obtained on the beam structure in hard soil conditions Mu = -85.5012 kN (support for) 4D19; Mu = 42.7506 kN (pedestal under) used 3D16; and Mu = 30,2581 kN (in the middle span) used 3D16; on medium soil Mu = 92.0741 kN (support for) 4D19; Mu = 46.03705 kN (lower pedestal) used 3D16; and Mu = 59.4276 kN (center span) used 3D16 + 1D13; on soft soil Mu = -107,842 kN (upper support) 5D19 was used; Mu = 53,921 kN (pedestal under) used 4D16; and Mu = 63.4546 kN (center span) used 4D16; Axial force occurs in the main column due to the combination of the three types of soil is not too significantly different, on hard soil = 337,949 kN, medium soil = 339,785 kN, soft soil = 342,954 kN, so column reinforcement in all three uses 12D22